Menjanda sebagai Model Resiliensi Perempuan - Sabariman, Hoiril; Kholifah, Siti (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
Women in rural Madura prefer to live alone as a widow after being left by husbands (divorced/deceased). This phenomenon is better known as a single mother. The single mother women perform dual roles in the family, namely public roles and domestic roles. This research focuses on the causes of women who prefer to be single mothers as well as their strategies in maintaining resilience in the family. The case study approach and qualitative methods are used to understand the phenomenon. The data show that several factors influence women in Ponteh village to live longer as single mothers than men after getting divorced. Firstly, wanting to raise their children, secondly, for women, divorce is a traumatic event, third, understanding of Islamic thought, fourth, social prestige. The resilience of single mothers is indicated by their multiple roles as women. Women are more active in productive activities as well as reproductive or domestic activities. The contribution of this article is to explain more about the single mother phenomenon in rural Madura.